Consensus guidelines for the management of intracranial meningioma for lowand middle-income countries - Syed Ather Enam; Mehar Masroor; Saqib Kamran Bakhshi; Fatima Shaukat; Hafiza Fatima Aziz; Kaynat Siddiqui; Mohammad Hamza Bajwa; Muhammad Shakir; Rabeet Tariq; Altaf Ali Laghari; et al. (Journal of the Pakistan Medical Association, 2024)
Intra-cranial meningiomas represent the most common type of extra-axial brain tumour in adults. Characteristically slow-growing and often asymptomatic, these tumours may only require observation in some cases. However, lesions that cause a significant mass effect necessitate intervention, primarily through surgical means. Additionally, in cases of significant unresectable low-grade residual meningioma or high-grade tumours, radiation therapy becomes essential. Notably, current management guidelines predominantly reflect data derived from high-income countries, failing to address constraints prevalent in the developing world, such as limited financial resources and restricted access to advanced surgical facilities. This manuscript introduces guidelines specifically tailored for the management of meningioma in patients from low- and middle-income countries, considering their unique healthcare challenges and resources. Keywords: Meningioma, brain neoplasms, health care, neurooncology.